2017
DOI: 10.1021/acsnano.6b07477
|View full text |Cite
|
Sign up to set email alerts
|

High-Rate Assembly of Nanomaterials on Insulating Surfaces Using Electro-Fluidic Directed Assembly

Abstract: Conductive or semiconducting nanomaterials-based applications such as electronics and sensors often require direct placement of such nanomaterials on insulating surfaces. Most fluidic-based directed assembly techniques on insulating surfaces utilize capillary force and evaporation but are diffusion limited and slow. Electrophoretic-based assembly, on the other hand, is fast but can only be utilized for assembly on a conductive surface. Here, we present a directed assembly technique that enables rapid assembly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…Indeed, several works have shown that even a single material system shows diverse structures and complex properties by carefully directing the self-assembly. [26][27][28] In addition to being model colloidal systems, nanoemulsions are widely used in applications such as food products, cosmetics, pharmaceuticals, and enhanced oil recovery for which the ability to engineer material properties through processing conditions is desirable. 29…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several works have shown that even a single material system shows diverse structures and complex properties by carefully directing the self-assembly. [26][27][28] In addition to being model colloidal systems, nanoemulsions are widely used in applications such as food products, cosmetics, pharmaceuticals, and enhanced oil recovery for which the ability to engineer material properties through processing conditions is desirable. 29…”
Section: Introductionmentioning
confidence: 99%
“…Rapid advances in high‐rate large‐area fabrication techniques are enabling new ways of realizing electronic devices. Along with a number of groups, we believe that revolutionary transistor design presents opportunities that are inaccessible to evolutionary developments, in terms of energy efficiency, gain, and large‐area manufacturability.…”
Section: Structural and Electrical Characteristics Of Source‐gated Trmentioning
confidence: 99%
“…[18,22] Interactions between the functional materials and regular solution features in their microliquid environment govern the formation of the structures. [23,24] Precise manipulation of multiphase flows during the micropatterning process is essential for heterogeneous integration of various functional materials. [25] This requires a reliable strategy to achieve microscale heterostructures by regulating liquid flows and interfaces, particularly for dots and lines due to their key role in building miniaturized and integrated operating systems.…”
Section: Lateral Functional Devicesmentioning
confidence: 99%
“…However, the difficulty of the manipulation of the dynamic flow of the solution in the microliquid patterning process leads to uncontrollable interfacing connection and low precision of composite micropatterns, resulting in poor device performance . Interactions between the functional materials and regular solution features in their microliquid environment govern the formation of the structures . Precise manipulation of multiphase flows during the micropatterning process is essential for heterogeneous integration of various functional materials .…”
mentioning
confidence: 99%